Etiological characteristics and practical lessons of a major outbreak of acute intestinal infection among migrant workers - A. A. Yakovlev; M. N. Pogromskaya; I. P. Fedunyak; V. B. Musatov; V. N. Kutuzov; I. V. Gorbova; L. A. Kaftyreva; Yu. N. Korzhaev; L. V. Petrova (Журнал инфектологии, 2014)
Acute intestinal infections remain a significant problem for the majority of economically developed countries. Acute intestinal infection disease incidence in the structure of infectious pathology steadily ranks the 2nd place after acute virus respiratory infections. The urgency of the acute intestinal infections problem is connected with the frequent occurrence of clusters of cases ( outbreaks ) .The last mass and the largest in the last 20 years outbreak of acute intestinal infection , was detected in St. Petersburg in 2013. The Russian Federation takes one of the first places in the world in the number of migrants. The usage of food , stored or cooked with violation of sanitary rules contributes to infection and a high prevalence of intestinal infections among migrants. In the process of medical care when analysing the outbreak among migrants a number of requirements and problems was revealed; solving these problems will make it possible to stop similar epidemic situations during the shortest period and at the lowest cost.